Taxes, Regulations, and the Value of U.S. and U.K. Corporations - McGrattan, Ellen R.; Prescott, Edward C. (Review of Economic Studies, 2005)
We derive the quantitative implications of growth theory for U.S. corporate equity plus net debt over the period 1960–2001. There were large secular movements in corporate equity values relative to GDP, with dramatic declines in the 1970's and dramatic increases starting in the 1980's and continuing throughout the 1990's. During the same period, there was little change in the capital—output ratio or earnings share of output. We ask specifically whether the theory accounts for these observations. We find that it does, with the critical factor being changes in the U.S. tax and regulatory system. We find that the theory also accounts for the even larger movements in U.K. equity values relative to GDP in this period.